Una aproximación al sexismo y a las brechas de género en la cultura académica de las mujeres universitarias de la sede Rodrigo Facio - Álvarez Espinoza, Nazira (2023)
We share experiences, reflections and lessons learned about the experience of sexism and gender gaps that pre-exist in theacademic culture of the Rodrigo Facio campus. The foregoing is product of two research projects developed by the authors and with inputs from the Gender Gaps and Sexism in University Life Conference held in June 2022. Despite the generational gaps, women in academic life continue to experience implicit or explicit sexist behaviors, values and structures that encourageit, so it is necessary to transform the academic life conditions of the female population in the university.